Salud laboral y salud mental en población trabajadora inmigrante Occupational health and mental health in migrant worker population - Macarena Gálvez Herrer; María Dolores Gutiérrez García; Nuria Zapico Martínez (Escuela Nacional de Medicina del Trabajo, 2011)
Partiendo de una conceptualización de la salud mental como un bienestar físico, psicológico y social, en el presente artículo revisaremos la situación de esa fuerza trabajadora atendiendo a la complejidad de su situación legal, social y laboral y cómo todo ello se relaciona con su salud mental y salud laboral. Working motivation is the main reason of the migratory phenomenon. It means breaking with cultural, social and language barriers, both in the society of origin as in the receiving. Migration processes do not themselves involve mental health problems, but they raise situations of high vulnerability and challenges of integration. Based on a conceptualization of mental health as the physical, psychological and social well-being, in the present article we will review the legal status, social and labour, and how this relates to their mental and occupational health.